PENGEMBANGAN PENUNTUN PRAKTIKUM KIMIA DASAR II TERINTEGRASI PROBLEM BASED LEARNING (PBL) DI UNIVERSITAS MUHAMMADIYAH TAPANULI SELATAN - Heni Mulyani Pohan (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2018)
AbstractThis study aims to: (1) analyze basic chemistry practicum II guides at UMTS, (2) develop basic PBL integrated chemistry practicum guides that are in accordance with the basic chemical syllabus II at UMTS, (3) to find out how the basic chemical practicum guide II influences integrated PBL towards students' knowledge, attitudes and skills. The sample of this study were 14 students of the fourth semester of chemistry education at Muhammadiyah University of South Tapanuli (UMTS). Before conducting research, the researcher first observes the field to analyze the UMTS II basic chemistry practicum guide. After researchers compiled a guide to basic chemistry practicum II integrated Problem Based Learning (PBL) was validated by 4 lecturers who were experts in their fields and then revised and then tested to the students. Based on the tabulation, the results of the feasibility test for integrated chemistry practicum II integrated PBL have an average of 3.88, which is feasible to use and the results of the feasibility test aspects of integrated practicum language PBL have an average of 3.75 which means it is worthy of use. The assessment results of the students' effectiveness in doing the practicum using PBL integrated II basic chemistry practicum guide that is equal to 2.05, namely the affective value of students is good and psychomotor assessment is obtained by an average of 2.36 as well as the good category. To assess the cognitive results of students the test was carried out in the form of a pretest and posttest with a pretest value of 69.29 and a posttest score of 83.57 to obtain a gain value of 0.46, namely the effectiveness of PBL integrated II basic chemistry practicum guide. Keywords: Basic Chemistry Practicum Guide Development, Problem Based Learning Model.